ANALISIS KELAYAKAN USAHA PENGOLAHAN IKAN SALAI DI KELURAHAN AIR DINGIN KECAMATAN BUKIT RAYA KOTA PEKANBARU PROVINSI RIAU (Studi Kasus Pada Usaha Ikan Salai Sedap Bakat) - Eka Marlena; Azharuddin M Amin (DINAMIKA PERTANIAN, 2022)
This study aims to analyze the characteristics of entrepreneurs and smoked fish business profile; availability, acquisition, and use of raw materials and supporting materials for smoked fish processing business; non-financial business feasibility and financial feasibility of smoked fish processing business; and the sensitivity of the smoked fish processing business. The method used in this research was a case study in the processing business of "Spiced Fish Bakat" in Air Dingin Village, Bukit Raya District, Pekanbaru City, Riau Province. This research was carried out for six months starting from January to June 2022. The respondents in this study were entrepreneurs and four workers. Data analysis was performed using quantitative and qualitative descriptive analysis (market and marketing aspects, technical aspects, environmental aspects, legal aspects, and management aspects, and financial aspects using four investment criteria (NPV, Net B/C, IRR, and Payback Period) and sensitivity analysis with the Switching Value approach. The results showed that the characteristics of entrepreneurs belong to the productive age with 46 years of age, 16 years of education (graduate) with 12 years of business experience, and 4 family members. Salai Sedap Bakat fish processing business is classified as a small-scale and household business and still uses traditional technology in the production process. Non-financial feasibility from market and marketing aspects, technical aspects, legal aspects, and management aspects of the salai fish business was feasible. The environmental aspect was not yet feasible because there is no provision for waste treatment from the by-products of smoked fish processing. Meanwhile, financially the Salai Sedap Bakat fish processing business is feasible to be continued and developed because it is profitable based on 4 investment criteria with an NPV of IDR 50,086,397 > 0, Net B/C with a value of 1.43 > 1, an IRR value of 21% > i ( 6.69%) and Payback Period for 4 years 1 month 5 days < business life (10 years). Based on sensitivity analysis using the switching value approach, the profit of the Salai Sedap Bakat Fish Business was more sensitive to the decline in the price of catfish production with a decrease in the NPV value of 90.65% and a decrease in the production of smoked catfish with a percentage of 90.28% compared with an increase in operational costs with a percentage of 82.36% of the base value.